School students' introduction to the world of work. Issue 1 (4th February 2014) - McKechnie, Jim; Howieson, Cathy; Hobbs, Sandy; Semple, Sheila
Abstract : Purpose: – The aim of this paper is to investigate the type of activities carried out by young people in a range of jobs that are typically undertaken by school students. The research examines opportunities for skill development in these jobs. Design/methodology/approach: – The research consisted of a nationally representative survey of school students. Multivariate analysis was used to examine the variables which predict the likelihood that a school student will be employed in a job which has a higher "job activity score" as measured by the frequency and number of activities undertaken. Findings: – In total, 38 per cent of school students were working at the time of the survey. The survey demonstrates the diversity of the employment experiences and the opportunities it provides for skill development. The analysis supports the view that this first exposure to employment may offer opportunities for skill development. Unlike previous research in Britain the study is able to explore the extent of variations between jobs. Practical implications: – The data demonstrates the extent to which school students combine full-time education with part-time employment and the value of this experience. This raises questions about whether schools should engage with naturally occurring employment experiences. Originality/value: – The paper uses a unique British data set to investigate what school students do in their part-time jobs, extending the hitherto limited research in this area. By addressing this issue the paper contributes to the debate regarding the value of this early exposure to the world of work.